Manajemen Pembelajaran Bahasa Jawa Menggunakan Moda Besmart UNY - Hartanto, Doni Dwi; Triyono, Sulis (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2021)
Besmart is an online learning model developed and used by Universitas Negeri Yogyakarta (UNY). This study aims to describe the management of Javanese language learning using the Besmart UNY mode. Learning management that is carried out is starting from the process of preparation, implementation, to learning assessment, as well as measuring the level of student satisfaction with learning management using the Besmart mode. The method used is descriptive-analytical. The instrument used to measure the level of student satisfaction is a questionnaire. Based on the results of research, learning management using the Besmart mode facilitates the implementation of learning management in Javanese language courses. Learning the Javanese language that has been considered very boring can be made more interesting by utilizing the features available at Besmart. The management of Javanese learning by maximizing the support of the information and communication technology in the Besmart mode helps achieve the Javanese language's objectives more optimally. The use of Besmart in learning management is proven to be very helpful for students (58,5%) and students are very satisfied (50,9%) with learning management with the Besmart mode.